Relación de las actividades visuales con el astigmatismo en niños de 6 a 8 años del colegio Rodrigo Lara Bonilla. (2020)
Objective: To determine the relationship between visual activities with astigmatism in a population of 6 to 8 years old in the city of Bogotá. Method: Cross-sectional study, carried out on 78 children in an educational institution. Visual examination was performed on all participants, and the refractive error was determined by cycloplegia. Visual activity was investigated by means of a questionnaire. Results: Emmetropic and astigmatism children spend more time watching television and doing homework, followed by activities such as computer / video games, outdoor activity / sports and finally reading for fun. Children diagnosed with severe astigmatism spend less time doing the activities investigated than the group with mild / moderate astigmatism. Conclusion: Most children spend most of their non-school time watching television, and the activity they spend the least time on is reading for fun. In the group of children with astigmatism, it was evident that the children with a severe diagnosis (cylinder> 3.00D), spent less time on all the activities investigated, which may be related to the fact that most of them did not use optical correction.